2006
DOI: 10.1212/01.wnl.0000223343.82809.cf
|View full text |Cite
|
Sign up to set email alerts
|

Excess of nonceruloplasmin serum copper in AD correlates with MMSE, CSF β-amyloid, and h-tau

Abstract: The authors' results confirm the existence of changes in copper component distribution, particularly the copper fraction unexplained by ceruloplasmin and support the hypothesis of a beta-amyloid and copper connection in Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
134
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(146 citation statements)
references
References 59 publications
11
134
0
1
Order By: Relevance
“…25 A hint towards this interpretation comes from our estimation-via a clearance measure-that about 3% of serum 'free' copper crosses the BBB in living patients and possibly interact with Aβ. 15 The latter finding was recently confirmed by other authors, who demonstrated an interaction between copper and Aβ in the CSF, 26 probably resulting in catalytic generation of peroxides (H 2 O 2 ) and Aβ aggregation, 15,26 ultimately leading to neurodegeneration. 27 Alternative hypotheses could be put forward to explain ceruloplasmin fragmentation in AD.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 68%
See 2 more Smart Citations
“…25 A hint towards this interpretation comes from our estimation-via a clearance measure-that about 3% of serum 'free' copper crosses the BBB in living patients and possibly interact with Aβ. 15 The latter finding was recently confirmed by other authors, who demonstrated an interaction between copper and Aβ in the CSF, 26 probably resulting in catalytic generation of peroxides (H 2 O 2 ) and Aβ aggregation, 15,26 ultimately leading to neurodegeneration. 27 Alternative hypotheses could be put forward to explain ceruloplasmin fragmentation in AD.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 68%
“…There is new evidence suggesting that brain copper may redistribute outside the neuronal cell, leaving it relatively deficient. 7 Although past studies in man have found no differences between AD and controls in serum copper levels, [8][9][10][11] more sophisticated measurements have recently shown both an increase, [12][13][14][15] and a decrease of these levels, 16,17 thus opening a debate on a toxic or protective role of copper in AD. Results from our laboratory, though, suggest that it is the ceruloplasmin-copper relationship, rather than the level of absolute (i.e., bound and not bound to ceruloplasmin) serum copper, that may be the key issue in interpreting in vivo copper findings in AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 A derangement of copper homeostasis leading to a labile pool may influence disease onset or progression. 4,5 This notion was initially claimed in several of our studies on the basis of evidence that a specific serum pool of copper, not bound to ceruloplasmin (also named ''free'' copper) was associated with some typical clinical signs and cerebrospinal fluid (CSF) markers of AD. 4,6 Recently some investigators 7 have strongly supported this notionby providing hard data demonstrating elevated levels of exchangeable Cu 2 + in samples of the AD brain correlating with tissue oxidative damage.…”
mentioning
confidence: 89%
“…4,5 This notion was initially claimed in several of our studies on the basis of evidence that a specific serum pool of copper, not bound to ceruloplasmin (also named ''free'' copper) was associated with some typical clinical signs and cerebrospinal fluid (CSF) markers of AD. 4,6 Recently some investigators 7 have strongly supported this notionby providing hard data demonstrating elevated levels of exchangeable Cu 2 + in samples of the AD brain correlating with tissue oxidative damage. 7,8 Labile copper, already reported as a marker of Wilson disease (WD) 9,10 -the paradigmatic disease of free copper toxicosis or intoxication-also has the potential to be a ''modifying'' or risk factor for AD.…”
mentioning
confidence: 89%